”Drømmen om å bli en annen”. (By)vandringens betydning i Tomas Espedals "Gå. Eller kunsten å leve et vilt og poetisk liv" - Tunkiel, Katarzyna (Folia Scandinavica Posnaniensia, 2012)
The paper gives an analysis of three functions of the protagonist’s wandering in the essayistic novel Gå. Eller kunsten å leveet vilt og poetisk liv (2006, Walk. Or the art of living a wild and poetic life) by the Norwegian author Tomas Espedal. The analysis is inspired by the interpretation of the novel by Finn Tveito (2010) and focuses primarily on wandering in urban space, in and around the cities of Bergen and Paris. The functions identified in the paper are: (city) wandering defined as a search of a metaphorical home, as acting realised on two different levels, and as a way to accept the protagonist's role as a writer. Apart from this, the paper is an attempt to portray the wanderer's identity as a postmodern man and an artist.